Strain engineering and thermal conductivity of a penta-BCN monolayer: A computational study - Dabsamut, Klichchupong; Thanasarnsurapong, Thanasee; Maluangnont, Tosapol; T-Thienprasert, Jiraroj; Jungthawan, Sirichok; Boonchun, Adisak (My University, 2021)
Two-dimensional (2D) pentagonal nanostructures have been caught research attention down to their electronic, optical, mechanical and thermal transport properties. Among them, the newly proposed ternary penta-BCN monolayer shows a great potential for piezoelectric materials according to intrinsic piezoelectricity and spontaneous polarization. Nevertheless, the effect of strain toward these properties of the penta-BCN has not been elucidated. In this study, using density-functional theory with the Perdew-Burke-Ernzerhof (PBE) functional, we have investigated the impact of a uniform biaxial strain on the electronic structure and the thermal conductivity of the semiconducting penta-BCN single sheet. The strain-free penta-BCN monolayer is mechanically and dynamically stable with an indirect band gap of 1.70 eV. The sheet is rather soft as judged from the low in-plane Young's moduli. The pentagonal structure is preserved up to the yielding point of 18.4%, beyond this point the irreversible transition into the dynamically unstable, honeycomb-like system is observed. In contrast, the penta-BCN has dynamically instability under the compressive strain as small as -4%. The PBE band gap of the penta-BCN monolayer could be tuned within a range of 1.36-1.70 eV, falling into the infrared spectrum. The calculated lattice thermal conductivity of penta-BCN is around 97 W m-1 K-1 at temperature of 300 K, and decreases with increasing temperature.
Keywords: penta-BCN; pentagonal; piezoelectric; strain; thermal conductivity